Effects of Text-messaging on the Academic Writing of Arab EFL Students - Al-Salman, Saleh M.; Saeed, Aziz T. (Research in Language, 2017)
This paper investigates the effect of text-messaging on Arab EFL learners’ English academic writing. It also investigates teachers’ attitudes and reactions to the presence of e-texting features in their students’ writing. Qualitative and quantitative methods of analysis were employed on data obtained from the following sources: (1) a sample of freshman students’ writing, (2) a survey investigating students’ use of e-chatting in Arabic and English, and (3) a questionnaire eliciting teachers’ reactions to students’ use of texting features in academic writing. The data were collected from a student sample of the Arab Open University (AOU). The research findings show that Arab EFL students’ writing does not reveal a heavy use of texting features, which suggests that this phenomenon neither poses a serious threat nor adversely impacts students’ written English.